Films and relationship problems. The road movie - Rico Caballo, Laura (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2014)
The article aims to contribute to the understanding of the therapeutic use of film and how it is applied in clinical practice. How and why the film can be suitably and effectively used in relationship problems seen from the therapeutic experience, opening a forum for sharing between professionals. Road movie is taken as example, and some practical exercises for individual or group workshops therapies that complement and accompany the cinematic experience are given.
Keywords: Therapy; couple; cineterapia; movies; creativity.